Effects of using augmented reality on students' learning - António Faria; Guilhermina Lobato Miranda (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
This article presents the results of a systematic review of the literature regarding the effects of using Augmented Reality (AR) on the learning of science students (Natural Sciences and Biology). The PRISMA methodology was used. Ten articles were selected from indexed journals, in a period of time between 2010 and 2022, after applying the inclusion and exclusion criteria. The main inclusion criteria were: only articles with students from Basic and Secondary Education (equivalent to ISCED 2 and 3) and that report results in students' learning. The main exclusion criteria were: duplicate articles and those that did not present a teaching strategy associated with the use of AR. The databases consulted were Scopus, ScienceDirect, Springer Link, EBSCO and Web of Science.  Eight out of ten of the selected articles used an experimental methodology. The results indicate that AR had positive effects on students' learning and motivation, as well as on other variables such as visuospatial skills and student involvement in tasks.